Breast Cancer Research - Bardia, Aditya; Huang, Jing.; Giles, Erin D.; Wellberg, Elizabeth A.; Lyons, Traci; Chodosh, Lewis; SpringerLink (Online service) (London : BioMed Central : Imprint: BioMed Central.)
Breast Cancer Research is an international, peer-reviewed online journal, publishing original research, reviews, editorials and reports. Open access research articles of exceptional interest are published in all areas of biology and medicine relevant to breast cancer, including normal mammary gland biology, with special emphasis on the genetic, biochemical, and cellular basis of breast cancer. In addition to basic research, the journal publishes preclinical, translational and clinical studies with a biological basis, including Phase I and Phase II trials.
Keywords: Cancer; Oncology; Cancer$1 (BTreatment.s; Cancer Biology; Oncology; Cancer Therapy